2013
DOI: 10.4049/jimmunol.1203161
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Prolonged Exposure to HIV Reinforces a Poised Epigenetic Program for PD-1 Expression in Virus-Specific CD8 T Cells

Abstract: Antigen-specific CD8 T cells play a critical role in controlling HIV infection but eventually lose antiviral functions in part because of expression and signaling through the inhibitory PD-1 receptor. To better understand the impact of prolonged TCR ligation on regulation of PD-1 expression in HIV-specific CD8 T cells we investigated the capacity of virus-specific CD8 T cells to modify the PD-1 epigenetic program following reduction in viral load. We observed that the transcriptional regulatory region was unme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
129
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(139 citation statements)
references
References 32 publications
10
129
0
Order By: Relevance
“…We have recently reported that the PD-1 transcriptional regulatory region underwent dynamic change in epigenetic programming during the development of functional memory and exhausted CD8 T cells. Specifically, we observed that functional memory CD8 T cells reacquired a methylated PD-1 promoter while the PD-1 promoter remained unmethylated in exhausted CD8 T cells even when viral loads were reduced to undetectable levels (25,26). These reports suggest that long-term antigen exposure enforces the demethylation of the PD-1 promoter in fully exhausted CD8 T cells.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…We have recently reported that the PD-1 transcriptional regulatory region underwent dynamic change in epigenetic programming during the development of functional memory and exhausted CD8 T cells. Specifically, we observed that functional memory CD8 T cells reacquired a methylated PD-1 promoter while the PD-1 promoter remained unmethylated in exhausted CD8 T cells even when viral loads were reduced to undetectable levels (25,26). These reports suggest that long-term antigen exposure enforces the demethylation of the PD-1 promoter in fully exhausted CD8 T cells.…”
mentioning
confidence: 61%
“…Our previous study revealed that PD-1 expression on exhausted CD8 T cells was coupled to DNA demethylation of the PD-1 transcriptional regulatory region (25). Interestingly, exhausted CD8 T cells retained the unmethylated PD-1 loci even when the viral load was reduced to undetectable levels at the late phase of mouse and human chronic infection (25,26). This study generated several important questions: was the retained demethylated state simply due to the persistence of a low level of antigen exposure?…”
Section: Discussionmentioning
confidence: 98%
“…Thus, in agreement with previous reports (55, 56), we conclude that expansion in IL-2 alters the expression of these markers and compromises the potential use of inhibitory receptors to select for tumor-reactive cells after in vitro expansion. Recent work in animal models suggests that chronic antigen stimulation (57)(58)(59) or a tolerizing microenvironment (60) may lead to permanent epigenetic changes in T cells, raising the possibility that the restoration of function observed in previously exhausted or tolerized cells in presence of cytokines may only be transient. These results have not yet been corroborated in human tumor-specific cells.…”
Section: Discussionmentioning
confidence: 99%
“…The de-methylation was maintained in antigen-specific T-cells long after LCMV clone-13 virus load has dropped below detectable levels in the blood 65 . A lack of methylation in the PD-1 promoter region has also been observed among antigen-specific CD8 T-cells from HIV patients which have been treated long-term (>2 years) with anti-retroviral therapy or in elite controllers 66 What remains unknown, however, is when T-cells undergo this differentiation. The incremental appearance of T-cells with an "exhausted" phenotype led to the conclusion that prolonged exposure to antigen and inflammation causes a progressively occurring acquisition of an exhausted phenotype 68 .…”
Section: T-cells Undergo Stable Differentiation In Persisting Infectimentioning
confidence: 99%